Determinants of Non-Alcoholic Beverages: A Case of Punjab Pakistan - Aslam, Manan; Latif, Shahid (Journal of Management and Research, 2017)
This current research endeavors to study important factors having a significant impact on consumer’s choice of beverages in Punjab province of Pakistan. Beverages in two major categories of ‘hot’ and ‘cold’ have been studied to examine consumer consumption pattern. Data has been collected through interview from 80 respondents belonging to these two major cities of Punjab i.e. Lahore and Faisalabad by incorporating stratified random sampling technique. These two cities of Punjab were selected because of their big departmental stores like Metro cash and carry store, ALFateh and others. A pre-tested and well-arranged questionnaire was used for data gathering from the respondents. To estimate the outcome of factors affecting the choices of consumers (demand function), multiple regression was incorporated. Results of this research showed that consumption pattern of cold beverages was affected significantly by consumer income, cold beverages prices, city selected for survey and number of adolescents in a family whereas factors which affected the consumption of hot beverages were food expenditure, living area, marital status, income, working persons in a family and family size. Due to availability of various brands of beverages, consumption is accelerating with the passage of time and consumers are willing to pay for beverages due to change in various socio-economics factors in the society. So, local industry should produce cost effective and quality drinks to enhance the usage.